REHABILITATION AFTER COCHLEAR IMPLANTATION (American Journal of Interdisciplinary Research and Development, 2024)
This article describes the importance of cochlear implantation and post-cochlear implantation for children with hearing loss. Special pedagogue: the work of deaf pedagogues and speech therapists on the hearing of preschool children and children with cochlear implants is disclosed.